SCALING THE GREAT FIREWALL OF CHINA: USES AND GRATIFICATIONS FOR CIRCUMVENTING STATE-IMPOSED INTERNET BOUNDARIES - Yeo, Tien Ee Dominic (AoIR Selected Papers of Internet Research, 2014)
This paper examines the motivation of Chinese Internet users for circumventing state- imposed Internet restrictions – a practice called fanqiang (to scale the Great Firewall of China). It fills an important gap in our knowledge of state-imposed Internet controls in China which has been dominated by discussions on technological dimensions and implications on the public sphere. Through a series of focus group interviews with Chinese Internet users in Guangzhou, the study in this paper found fanqiang to be driven by more deliberative motives – largely information-seeking but also, to a smaller extent, entertainment and social utility. Our findings clarify the nature of users’ information-seeking motive for fanqiang. Unsurprisingly, research participants reported that they fanqiang to search for news outside China, expressing their distrust of the account of the official media on events in the country. But contrary to conventional wisdom, we found that the desire for political or other forms of sensitive content was not the most salient motive for circumventing Internet restrictions. The desire for politically sensitive information was largely driven by curiosity rather than personal values; it was stronger when individuals initially fanqiang but is attenuated after the initial novelty of the “forbidden fruit” wears off. Furthermore, the information routinely sought by research participants outside the Great Firewall was neither politically sensitive nor falling within the officially expressed categories of undesirable materials. Overall, our findings suggest that the desire for more complete knowledge provides a clearer picture of Chinese Internet users’ information-seeking motive for fanqiang.